Handbook of biofuels - Sahay, Sanjay (Academic Press, 2022)
"Handbook of Biofuels looks at the many new developments in various type of bioenergy as well as the significant constraints in their production and/or applications, and the hurdles to overcome. Beyond introducing current approaches and possible future directions of research, this book covers sources and processing of raw materials to downstream processing, constraints involved and research approaches to address and overcome these needs. With chapters on the techno-economic analysis of biofuel production and concepts and step-by-step approaches in bioenergy processing, the objective of this book is to present a comprehensive and all-encompassing reference about bioenergy to students, teachers, researchers, and professionals"--Print verion, page 4 of cover.